Analysis of Position of Itinerant Teachers In Service Delivery Model of Education: The Impact of Shifting Placement on Itinerant Teachers in Educational Settings (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Many research studies have investigated the position ofan itinerant teacher of students who are deaf or hard of hearing in whichanalysis of the advantages and disadvantages of the service delivery model ofitinerant teaching have been considered. Because there has been a “shift in placement for students who are deafor hard of hearing into more mainstream settings, there has been a specificincrease in the number of itinerant teachers and a comparable decrease in thenumber of self-contained classroom teachers” (Miller, 2000).